Insights into the impacts of and responses to COVID-19 pandemic: The South African food retail supply chains perspective - Osayuwamen Omoruyi; Edward A. Dakora; Olugbenga O. Oluwagbemi (Journal of Transport and Supply Chain Management, 2022)
Background: With the observed cases of the coronavirus disease 2019 (COVID-19) pandemic in South Africa, coupled with varying levels of national lockdowns, food retail supply chains in South Africa were adversely affected. The pandemic affected international travel, global logistics, supplier production and stockpiles at the supply end, which resulted in shortages at retailers and increased prices for basic food items.